2014
DOI: 10.1111/jvim.12442
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Bleeding in Dogs from Grenada Seroreactive to Anaplasma platys and Ehrlichia canis

Abstract: BackgroundFrequent exposure of Grenadian dogs to Rhipicephalus sanguineus results in Anaplasma platys, and Ehrlichia canis seroreactivity. During elective surgeries, substantial intraoperative hemorrhage occurs in some seroreactive dogs.ObjectivesTo assess hemostatic parameters and bleeding tendencies as well as prevalence of PCR positivity in apparently healthy A. platys and E. canis seroreactive and seronegative free‐roaming dogs from Grenada.AnimalsForty‐seven elective surgery dogs allocated to 4 groups: Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
6
17
1
Order By: Relevance
“…Nevertheless, other studies have demonstrated that other tissues besides the spleen are better in detecting E. canis by PCR. For example, some authors describe results similar to those obtained in the present study and show that E. canis DNA was most often ampli ed from bone marrow [52,53]. But, in these cases, there was experimental disease, and PCR was performed using aspirates.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, other studies have demonstrated that other tissues besides the spleen are better in detecting E. canis by PCR. For example, some authors describe results similar to those obtained in the present study and show that E. canis DNA was most often ampli ed from bone marrow [52,53]. But, in these cases, there was experimental disease, and PCR was performed using aspirates.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, other studies have demonstrated that other tissues besides the spleen are better in detecting E. canis by PCR. For example, some authors describe results similar to those obtained in the present study and show that E. canis DNA was most often ampli ed from bone marrow [51,52]. But, in these cases, there was experimental disease, and PCR was performed using aspirates.…”
Section: Discussionsupporting
confidence: 86%
“…Bleeding diathesis is also more common and severe in the chronic phase of CME, and in those dogs with concurrent bleeding-predisposing conditions (e.g. infection with L. infantum, A. platys infection, von Willebrand's disease, drug-induced or uremic thrombocytopathy) [38,40]. It is manifested typically as cutaneous and mucosal petechiae and ecchymoses, hyphema, epistaxis, hematuria, melena, prolonged bleeding from venipuncture sites or intraoperative bleeding [16,19,40,41] (Figures 1-4).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Two previous studies indicated that spleen specimens were of higher sensitivity compared to BM or blood for the confi rmation of subclinical CME [52] and the evaluation of the response to treatment [52,80]. However, other studies, have suggested that the spleen was inferior to other tissues [40,71,77,81].…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%